The Influence of Products, Prices, and Places on Parents' Decision to Choose a Kindergarten Preschool Mediated by Trust in South Kuta District - I Ketut Yogi Angga Pratama PUTRA; Ni Made WAHYUNI; Ni Luh Putu INDIANI (International Journal of Environmental, Sustainability, and Social Science, 2025)
Preschool education plays a vital role in shaping children's development and personality. Awareness of its importance continues to grow, reflected in the increasing number of preschool institutions, particularly in South Kuta District. However, this growth has intensified competition among preschools in attracting students. Therefore, research is needed to analyze the factors influencing parents' decisions in selecting a preschool. This study examines the impact of product, price, and place on purchasing decisions, with trust as a mediating variable. The population consists of parents seeking preschool enrollment for their children in South Kuta District. Using a questionnaire, data were collected from 110 respondents and analyzed with Partial Least Square (PLS) inferential analysis. Findings reveal that product and price have a positive and significant effect on purchasing decisions and trust. While place significantly affects trust, its impact on purchasing decisions is positive but not significant. Trust partially mediates the relationship between product and purchasing decisions, as well as between price and purchasing decisions. However, trust fully mediates the relationship between place and purchasing decisions. These results highlight the importance of product quality, pricing strategies, and trust-building efforts in attracting parents to preschool institutions.